1990
DOI: 10.1111/j.1432-1033.1990.tb19365.x
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of insulin in isolated liver endosomes is functionally linked to ATP‐dependent endosomal acidification

Abstract: The degradation of insulin in isolated liver endosomes and the relationships of this process with ATP-dependent endosomal acidification have been studied. Incubation of endosomal fractions containing 1251-insulin in isotonic KCl at 30°C resulted in a rapid loss of insulin integrity as judged from trichloroacetic acid precipitability, Sephadex G-50 chromatography, immunoreactivity and receptor binding ability, with a maximum at pH 5 -6 ( t 1 , 2 : 10, 10, 6 and 6 min, respectively). On a log/log plot, the amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 65 publications
6
32
0
Order By: Relevance
“…high (glucagon) (16,17), moderate (insulin) (4,30) and low (EGF and prolactin) (31). Using an alternate approach in which hydrolysis was measured by the generation of degradation products from unlabeled peptides, we have confirmed that EGF and insulin hydrolysis, but not glucagon hydrolysis, appears to be limited.…”
Section: Discussionsupporting
confidence: 51%
“…high (glucagon) (16,17), moderate (insulin) (4,30) and low (EGF and prolactin) (31). Using an alternate approach in which hydrolysis was measured by the generation of degradation products from unlabeled peptides, we have confirmed that EGF and insulin hydrolysis, but not glucagon hydrolysis, appears to be limited.…”
Section: Discussionsupporting
confidence: 51%
“…Thus, the removal of Arg from Arg-extended peptides within the endosomal compartment may be highly selective. The present observation agrees well with our previous studies on the endosomal proteolysis of internalised human proinsulin (HPI) that show that rat liver endosomes produce selective cleavages in the Glu 33 -Lys 64 C-peptide without apparent modification of arginyl-peptide bonds [6]. Previously, other studies have reported that Triton X-100 solubilised rat liver endosomes [4] and rat hepatoma Fao cells stably transfected with HPI [5] processed HPI to des- [31,32]-HPI without conversion into mature HI.…”
Section: Discussionsupporting
confidence: 93%
“…While insulin was subject to rapid endosomal ligand dissociation and degradation [16,19,33], reduced in vivo and cell-free endosomal processing was observed with the H2-analogue [14,24,26] and proinsulin [6]. An altered IR phosphotyrosine profile was also observed at the endosomal locus, with this process being higher (H2-analogue) and of longer duration (H2-analogue and proinsulin) [6,14,24].…”
Section: Discussionmentioning
confidence: 99%
“…For some, degradation takes place early in the endocytic pathway. This is the case for polypeptide hormones such as insulin (2)(3)(4), glucagon (5), and parathyroid hormone (6) and growth factors such as the epidermal growth factor (7) and insulin-like growth factor-I (IGF-I) 1 (8) as well as endocytosed protein antigens for major histocompatibility class II presentation (9) and plant toxins (10).…”
Section: -24mentioning
confidence: 99%